Comprehensive Analysis of the Aldehyde Dehydrogenase Gene Superfamily in Cassava (Manihot esculenta): Genome-Wide Identification and Transcriptional Insights: Genome-wide analysis of the ALDH genes in cassava - Tran, Vinh Thanh; Le, Man Thi; Nguyen, Anh Thi Ngoc; Dong, Huy Gioi; Le, Quynh Thi Ngoc; Cao, Phi Bang; Chu, Ha Duc (Journal of Tropical Life Science, 2025)
Aldehyde dehydrogenases (ALDHs) are a vital enzyme superfamily involved in cellular detoxification, metabolism, and stress responses in plants. Despite their known roles in various species, a comprehensive genome-wide analysis of the ALDH gene superfamily in cassava (Manihot esculenta), a key drought-tolerant crop, remains limited. This study systematically identified and characterized 29 ALDHs in the cassava genome, classifying them into distinct families based on sequence similarity and phylogenetic relationships. Structural and physicochemical analysis revealed notable variations in gene length, exon-intron organization, and protein properties, indicating functional diversity within the family. Of our interest, expression profiling across 11 different organs/tissues showed that several ALDHs exhibit tissue-specific expression patterns, suggesting their potential roles in diverse physiological processes. Moreover, transcriptomic analysis under drought stress conditions revealed significant changes in ALDH gene expression, with specific members being strongly up-regulated and down-regulated, implying their involvement in drought tolerance mechanisms. The findings provide new insights into the potential roles of ALDHs in cassava's ability to mitigate oxidative stress and enhance drought resilience. This study serves as a foundation for further functional characterization of ALDHs and offers valuable genetic resources for breeding programs aimed at improving cassava’s adaptation to environmental stresses. Understanding these genetic mechanisms will contribute to developing stress-resistant cultivars, ensuring sustainable cassava production in drought-prone regions.